Halal Certification Governance and Consumer Protection in Indonesia’s Digital Marketplace - Naisha Aluna Prameswari; Kai Alexander Wijaya; Ayla Seraphina Maharani (JUSTISIA GLOBAL EDUKASI, 2026)
The rapid expansion of digital commerce has transformed consumer behavior and business transactions in Indonesia, creating new challenges for halal assurance and consumer protection. This study examines the governance of halal certification within Indonesia’s digital marketplace and its implications for consumer rights and legal certainty. Using a normative approach grounded in Islamic legal modernism, the research analyzes the interaction between halal certification regulations, digital commerce practices, and consumer protection frameworks. The findings indicate that halal certification serves not only as a religious compliance mechanism but also as an instrument for ensuring transparency, product reliability, and consumer trust in online transactions. However, the digital marketplace presents regulatory challenges related to cross-border trade, product verification, information asymmetry, and enforcement limitations. The study reveals that effective halal governance requires coordination among regulatory authorities, certification institutions, digital platforms, and business actors. Furthermore, digital technologies offer opportunities to strengthen traceability, transparency, and public access to halal information. From the perspective of Islamic legal modernism, halal regulation should adapt to technological developments while preserving the ethical objectives of Islamic law. The research argues that consumer protection in digital markets depends on both effective regulatory oversight and the integration of Islamic ethical principles into commercial governance. The study concludes that strengthening halal certification governance can enhance legal certainty, consumer confidence, and market integrity in Indonesia’s growing digital economy. These findings contribute to contemporary discussions concerning Islamic commercial law, digital governance, and consumer protection in Muslim-majority societies.